Pengaruh Massage Effleurage Terhadap Penurunan Nyeri Kala I Pada Ibu Bersalin Di Klinik Pratama Citra Adinda - Analisa, Analisa; Sulastri, Mepi; Rossita, Taufianie (Jurnal Pakar Kesehatan, 2025)
Labour pain is the most severe of all pains, medically assessed as sharp and hot or somatic - sharp and burning. Severe pain in labour causes the mother to experience psycholgical disorders and depression. Labour pain can be controlled with non-pharmacological methods Effleurage Massage. The purpose of this study was to find out the effect of effleurage massage on decreasing first stage pain in labouring mothers at the Pratama Citra Adinda clinic.This research is a quantitative study using a preexperimental design. In this study researchers used the One-Group Pretest-Posttest Design method, namely in this design there was a pretest and Posttest before and after being given effleurage massage treatment. The sample in this study amounted to 33 people and data analysis using univariate and bivariate. The results of this study indicate that before effleurage massage, it was found that a small proportion of respondents 24.2% experienced mild pain and most respondents 75% experienced moderate pain. After the effleurage massage, it was found that almost half of the respondents 27.3% did not experience pain and some 72.7% experienced mild pain. So that there is an effect of effleurage massage on reducing pain during the first time in labour with the value of the statistical test used is the Wilcoxon test and obtained a significance value of p value = 0.000 (<0.05) means that there is a difference that gives pain before and after.There is an effect of Massage Effleurage on the pain level of labour during the active phase I. It is expected that Massage Effleurage can be done as one of the methods to reduce the pain level of labouring women during the active phase.